2021
DOI: 10.1016/j.ejca.2021.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Baseline co-medications may alter the anti-tumoural effect of checkpoint inhibitors as well as the risk of immune-related adverse events

Abstract: As gut microbiota composition is an important determinant of response to immune checkpoint inhibitors (ICIs), we examined the effect of various co-medications known for their interaction with microbiota, when given at ICI initiation. Patients and methods: We identified patients with advanced cancer treated with ICI between May 2015 and September 2017 in our institution. Co-medications given within 1 month before or 1 month after the first administration of ICI were reviewed from medical records. Survival data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 42 publications
3
59
0
Order By: Relevance
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 33 studies, of which 24 were peer-reviewed journal publications and 9 were conference abstracts, were included in the systematic review and meta-analysis. 12 , 13 , 19 49 The flow diagram of identifying the eligible studies is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 513 (21.5%) patients were with concomitant use of statin. Four studies reported the association between concomitant statin and survival outcomes with univariate analyses [ 15 , 23 , 26 , 28 ], while the other four studies reported with multivariate analyses [ 24 , 25 , 27 , 29 ]. Variables including demographic features, cancer characteristics, and smoking history were adjusted in the multivariate models.…”
Section: Resultsmentioning
confidence: 99%
“…The 3-hydroxy-3-methylglutaryl CoA (HMG-CoA) reductase inhibitors, also named as statins, are well-applied lipid-lowering medications [ 14 ]. Statins are commonly prescribed for patients with atherosclerosis and cardiovascular diseases, and about one-fifth of cancer patients receiving ICIs are also on statins [ 15 ]. Accumulating evidence shows that statins may also exert anticancer efficacy via multiple pharmacological mechanisms such as antiproliferation, anti-inflammation, proapoptosis, and anti-invasion [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors analysed the influence of comedications (including PPIs) on the anti-tumour effect and safety of these CPI. PPIs were prescribed in 38% of these patients; the median OS of patients receiving PPIs was 9 months versus 26.5 months in those not receiving PPIs (HR: 1.70, 95%CI: 1.40–2.08) [ 64 ].…”
Section: Ppis and Oncologic Treatment Efficacymentioning
confidence: 99%